Efficient Pd‐Catalyzed Direct Coupling of Aryl Chlorides with Alkyllithium Reagents. (3rd September 2020) - Scherpf, Thorsten; Steinert, Henning; Großjohann, Angela; Dilchert, Katharina; Tappen, Jens; Rodstein, Ilja; Gessner, Viktoria H.
Abstract: Organolithium compounds are amongst the most important organometallic reagents and frequently used in difficult metallation reactions. However, their direct use in the formation of C−C bonds is less established. Although remarkable advances in the coupling of aryllithium compounds have been achieved, Csp 2 −Csp 3 coupling reactions are very limited. Herein, we report the first general protocol for the coupling or aryl chlorides with alkyllithium reagents. Palladium catalysts based on ylide‐substituted phosphines (YPhos) were found to be excellently suited for this transformation giving high selectivities at room temperature with a variety of aryl chlorides without the need for an additional transmetallation reagent. This is demonstrated in gram‐scale synthesis including building blocks for materials chemistry and pharmaceutical industry. Furthermore, the direct coupling of aryllithiums as well as Grignard reagents with aryl chlorides was also easily accomplished at room temperature. Abstract : A general protocol for the Pd‐catalyzed coupling of aryl chlorides with alkyllithium reagents is reported. The use of the ylide‐substituted phosphine joYPhos allowed for high selectivities at room temperature, thus minimizing side reactions typical for these highly reactive reagents. This was demonstrated for a large substrate scope including the gram‐scale synthesis of building blocks for pharmaceutical industry.